A comparative study using different classifiers for face verification - Nazeer, Shahrin Azuan (2007)
Face recognition, verification and identification are often confused. Face recognition is a general topic that includes both face identification and face verification (also called authentication). On one hand, face verification is concerned with validating a claimed identity based on the image of a face, and either accepting or rejecting the identity claim (one-to-one matching).